J. Argyris Foundation Scholarship - Markou, George (My University, 2026)
A three-year scholarship from the J. Argyris Foundation to a Ph.D. student for the completion of his thesis. Dr Markou was the first ever recipient of this scholarship.
Keywords: Sciences